ANALISIS LOCUS OF CONTROL, ORIENTASI TUJUAN PEMBELAJARAN, DAN LINGKUNGAN KERJA TERHADAP SELF EFFICACY DAN TRANSFER PELATIHAN PEGAWAI DI KANTOR PT. KERETA API (Persero) DAERAH OPERASI V PURWOKERTO - Nurul Hasanah (Pro Bisnis, 2011)
This research is conducted at PT. Train ( Persero) Area Operate for V Purwokerto, with title : " Influence of Locus Control of, Orient the Target of Study, and Environment Work To Self Efficacy and Transfer Training of Officer in Office of PT. Train Area Operate For V Purwokerto" Target of this Research is to know influence of conrol of locus, orient the target of environment and study work to efficacy self and transfer training of Officer in Office of PT. Train Area Operate For V Purwokerto. used Analyzer by Structural Equation Modelling ( SEM). Of research result and data analysis obtained conclusion that: Of control Locus have an effect on by isn't it to efficacy self and training transfer. Mean excelsior of Locus control of in the reality excelsior also efficacy self and transfer training of officer of Office of PT. Train ( Persero) Area Operate For V Purwokerto. Orient target have an effect on isn't it to control of locus and transfer training of officer Mean good progressively orientation of target of in the reality excelsior of Locus control of and transfer training of officer of Office of PT. Tr ain ( Persero) Area Operate For V Purwokerto. Environmental of job have an effect on by isn't it to efficacy self and training transfer. Mean good progressively environment work in the reality excelsior of self transfer and efficacy training of officer of Office of PT. Train (Persero) Area Operate For V Purwokerto. Self Efficacy have an effect on by isn't it to training transfer. Mean excelsior of self efficacy in the reality excelsior of[is transfer of training of officer of Office of PT. Train ( Persero) Area Operate for V Purwokerto